Weighted composition operators on multidimensional Lorentz spaces and a glimpse on multipliers between bounded p-variation spaces (2018)
In this thesis we study the multidimensional Lorentz spaces via the two-dimensional decreasing rearrangement. In particular, results of interpolation, quasinormability and completeness are stablished, and weights that define a norm are characterized. The boundedness, compactness and closed range of the weighted composition operator defined on those spaces are also characterized. Finally, we present the Bounded $p$-variation spaces in the Wiener's sense, and then we characterize the set of multipliers between them.